The Role of Authentic Texts in Listening Skills (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article considers the definition of the essence of authentic materials and their role in teaching listening skills. Teaching students to listen to foreign language and understand it is one of the most important goals of teaching foreign languages. Therefore, this article discusses the main problems of listening, ways to solve these problems, and the role of authentic texts in teaching listening.